Diagnosis of critical thinking of elementary school students in Chimbote, Peru - Pérez-Morán, Graciela (2021)
Objective. To determine the level of development of the critical thinking of the students of the Educational Institutions of primary education of Chimbote. Materials and methods. A descriptive study was carried out in Chimbote, 2016. Critical thinking was evaluated in 250 boys and girls who belong to the sixth grade of primary education in 2016. A questionnaire of 30 questions aimed at addressing the dialogic and substantive dimensions was applied; each question included 5 response options on the Likert scale (1 = total disagreement up to 5 = total agreement). These variables were re-categorized by scaling by percentiles classified into three categories: (a) high, between 150-100 points; (b) medium, between 99-50; and (c) low, between 49-0 points. A descriptive analysis of the critical thinking variable was carried out according to its substantive and dialogic dimensions through tables with their relative and absolute frequencies. Results. There is a negative tendency in the development of critical thinking which is integrated the dimensions of substantive and dialogical, being the lowest level the one that obtained the highest percentage with 54% compared to the high level with 4.4%. Conclusion. There is a deficit of critical thinking in student body students and in for their substantive and dialogical dimensions.